Angled-stencil lithography based metal mesh/Ti3C2Tx MXene hybrid transparent electrodes for low-power and high-performance wearable thermotherapy. Issue 19 (4th May 2021) - Hossain, Mozakkar; Sibin, K. P.; Rao, K. D. M.
Abstract : Transparent and wearable devices have aroused immense research interest for their widespread applications, however, the fabrication of homogeneous devices is an outstanding challenge to manifest low-power wearable thermotherapy devices. Abstract : Transparent and wearable devices have aroused immense research interest for their widespread applications, however, the fabrication of electrically and thermally homogeneous devices is an outstanding challenge to manifest low-power wearable thermotherapy devices. Here, we developed simple angled-stencil lithography to fabricate Ag micro-mesh based transparent conducting electrodes (TCEs) and demonstrated a low sheet resistance of 0.8 Ω □ −1 and high transmittance of 83%, benefiting from the seamless junctions and highly aligned microstructures. The synergy between 2D Ti3 C2 T x MXenes and Ag micro-mesh elucidated electrical and thermal uniformity of the hybrid TCEs with a high figure of merit (FOM) value of 1.5 × 10 3 . The hybrid Ag micro-mesh/Ti3 C2 T x MXene heaters are mechanically robust and exhibited a homogeneous temperature distribution (∼99 °C) with a fast response time (18–28 s). The efficient Joule heating of Ag micro-mesh and perfect thermal management of Ti3 C2 T x MXenes together unraveled unprecedented thermal resistance (675 °C cm 2 W −1 ) and record-low actuation voltage (1.2 V). The hybrid transparent heater is successfully employed on a human wrist as a skin-mountable thermotherapy device while the low-power consumption enabled portability for transit mode operation. The low-power consumption and portability of hybrid TCEs empower next-generation wearable thermotherapy applications.